Comparison of 3D Cube FLAIR with 2D FLAIR for Multiple Sclerosis Imaging at 3 Tesla - Patzig, M.; Burke, M.; Brückmann, H.; Fesl, G. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: Three-dimensional (3 D) MRI sequences allow improved spatial resolution with good signal and contrast properties as well as multiplanar reconstruction. We sought to compare Cube, a 3 D FLAIR sequence, to a standard 2 D FLAIR sequence in multiple sclerosis (MS) imaging.Materials and Methods: Examinations were performed in the clinical routine on a 3.0 Tesla scanner. 12 patients with definite MS were included. Lesions with MS-typical properties on the images of Cube FLAIR and 2 D FLAIR sequences were counted and allocated to different brain regions. Signal-to-noise ratios (SNR) and contrast-to-noise ratios (CNR) were calculated.Results: With 384 the overall number of lesions found with Cube FLAIR was significantly higher than with 2 D FLAIR (N = 221). The difference was mostly accounted for by supratentorial lesions (N = 372 vs. N = 216) while the infratentorial lesion counts were low in both sequences. SNRs and CNRs were significantly higher in CUBE FLAIR with the exception of the CNR of lesion to gray matter, which was not significantly different.Conclusion: Cube FLAIR showed a higher sensitivity for MS lesions compared to a 2 D FLAIR sequence. 3 D FLAIR might replace 2 D FLAIR sequences in MS imaging in the future.Key points:Citation Format:• Patzig M, Burke M, Brückmann H et al. Comparison of 3D Cube FLAIR with 2D FLAIR for Multiple Sclerosis Imaging at 3 Tesla. Fortschr Röntgenstr 2014; 186: 484 – 488
Keywords: MR imaging; multiple sclerosis; 3 D imaging; FLAIR